Diversifikasi Produk Melalui Peningkatan Keterampilan Pembuatan Telur Asin Dari Telur Itik Dengan Varian Rasa Di Desa Manarap Baru Kalimantan Selatan - Defin Shahrial Putra; Kumara Efrianti; Mujiburrahman - (Jurnal Publika Pengabdian Masyarakat, 2020)
Duck eggs are known to have a more fishy odor than chicken eggs, so they are used to make fewer types of food. Though the nutritional content is quite good, duck eggs contain energy, protein, fat, carbohydrates which are higher than chicken eggs. Besides duck eggs also contain many vitamins including vitamin B-6, vitamin B-12, vitamin A, vitamin E, thiamin, riboflavin, niacin, folate. By processing duck eggs into salted eggs, the shelf life becomes longer, can add flavor. In addition, duck eggs have larger pores making it suitable to be salted eggs because the salt penetration process will take place better.This activity was motivated by the number of housewives in the village of Manarap Baru, South Kalimantan, precisely in Komp. Bumi Wahyu Utama IV. The purpose of this activity is to improve skills in making salted eggs plus flavor variants in the target group of housewives in the new village of Manarap. The activity was carried out for 8 months with several meetings, the number of participants was 16 housewives. The method used is training accompanied by lectures, demonstrations and practice. The results of this improvement in skills are to provide knowledge to housewives in the process of processing salted eggs using purebred chicken eggs and by adding flavor variants. Keywords: Diversification, Skills, Salted Eggs, Taste Variety.